1992
DOI: 10.1007/bf00054562
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive efficacy and effects of nitrendipine on cardiac and renal hemodynamics in mild to moderate hypertensive patients: Randomized controlled trial versus hydrochlorothiazide

Abstract: In this study antihypertensive efficacy, safety, and the effects of short-term nitrendipine administration on central and renal hemodynamics were evaluated in mild to moderate hypertensives. Our final goal was to ascertain whether the reduction in blood pressure induced by nitrendipine treatment was associated with maintained renal function. After a run-in period with placebo, 26 hypertensives without cardiac or renal disease were randomly assigned to a double-blind 8-week controlled trial with nitrendipine (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…All patients were maintained on a diet containing 150 mmol sodium per day. Using somewhat less reliable methods to measure renal plasma flow and glomerular filtration rate, they found a significant fall in renal vascular resistance without changes in flow, filtration rate, and filtration fraction at the end of the study period [3]. Despite the differences in methodology, the data all point in the same direction: Long-term treatment with a thiazide drug induces a favorable renal hemodynamic response in maintaining renal function.…”
Section: Antihypertensive Drugs and Renalmentioning
confidence: 59%
“…All patients were maintained on a diet containing 150 mmol sodium per day. Using somewhat less reliable methods to measure renal plasma flow and glomerular filtration rate, they found a significant fall in renal vascular resistance without changes in flow, filtration rate, and filtration fraction at the end of the study period [3]. Despite the differences in methodology, the data all point in the same direction: Long-term treatment with a thiazide drug induces a favorable renal hemodynamic response in maintaining renal function.…”
Section: Antihypertensive Drugs and Renalmentioning
confidence: 59%
“…As other targets of HCTZ in the model, we considered constant levels of urea and potassium in the blood. Since HCTZ increases blood urea and decreases blood potassium ( Scaglione et al, 1992 ; Scaglione et al, 1995 ; Devineni et al, 2014 ), we multiplied these parameters by the factors and (the modules “Hormonal system” and “Aldosterone”, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…In the model, we consider two dosages of aliskiren, 150 and 300 mg. If we denote the corresponding indicators of the drug as Aliskiren 150 and Aliskiren 300 , then the value of DRI is calculated by the formula: et al (1996) taking into account the following long-term dynamics: PRA increases by 45% (Villamil et al 2007); HR, ECFV, GFR, and CO do not significantly change (van Brummelen et al 1980, Shah et al 1978, Scaglione et al 1992, Scaglione et al 1995 (1996).…”
Section: Modeling Antihypertensive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Instead, there is some controversy as to the intrarenal haemodynamic effects of second generation dihydropyridinic calcium antagonists, as their vasodilatory effect on the efferent arteriole may vary according to the drug used. [16][17][18][19][20][21][22][23][24] In particular, the results of some studies suggest that amlodipine (AML) does not significantly reduce postglomerular resistances, 20,[22][23][24] whereas others have shown that amlodipine, nitrendipine (NIT) and other second-generation dihydropyridinic calcium antagonists induce haemodynamic variations suggesting a mainly efferent vasodilatory effect. [16][17][18][19]21 Unfortunately, as the method is highly complex, it has only been possible to carry out studies of the intrarenal haemodynamic effects of antihypertensive drugs on relatively small patient samples, and the assumption that calcium antagonists in general have only limited efficacy in reducing glomerular hyperfiltration has remained strong.…”
Section: Introductionmentioning
confidence: 99%